Long-Term Exposure to Particulate Air Pollution, Black Carbon, and Their Source Components in Relation to Ischemic Heart Disease and Stroke - Ljungman, Petter L. S. (Environ Health Perspect, 2019)
BACKGROUND: Long-term exposure to particulate matter (PM) in ambient air has been associated with cardiovascular mortality, but few studies have considered incident disease in relation to PM from different sources. OBJECTIVES: We aimed to study associations between long-term exposure to different types of PM and sources, and incident ischemic heart disease (IHD) and stroke in three Swedish cities. METHODS: Based on detailed emission databases, monitoring data, and high-resolution dispersion models, we calculated source contributions to PM with aerodynamic diameter [Formula: see text] ([Formula: see text]), PM with aerodynamic diameter [Formula: see text] ([Formula: see text]), and black carbon (BC) from road wear, traffic exhaust, residential heating, and other sources in Gothenburg, Stockholm, and Umeå. Registry data for participants from four cohorts were used to obtain incidence of IHD and stroke for first hospitalization or death. We constructed time windows of exposure for same-year, 1- to 5-y, and 6- to 10-y averages preceding incidence from annual averages at residential addresses. Risk estimates were based on random effects meta-analyses of cohort-specific Cox proportional hazard models. RESULTS: We observed 5,166 and 3,119 incident IHD and stroke cases, respectively, in 114,758 participants. Overall, few consistent associations were observed between the different air pollution measures and IHD or stroke incidence. However, same-year levels of ambient locally emitted BC (range: [Formula: see text]) were associated with a 4.0% higher risk of incident stroke per interquartile range (IQR), [Formula: see text] [95% confidence interval (CI): 0.04, 7.8]. This association was primarily related to BC from traffic exhaust. [Formula: see text] (range: [Formula: see text]) and [Formula: see text] (range: [Formula: see text]) were not associated with stroke. Associations with incident IHD were observed only for [Formula: see text] exposure from residential heating. DISCUSSION: Few consistent associations were observed between different particulate components and IHD or stroke. However, long-term residential exposure to locally emitted BC from traffic exhaust was associated with stroke incidence. The comparatively low exposure levels may have contributed to the paucity of associations. https://doi.org/10.1289/EHP4757